KONSEP MANUSIA DAN PROBLEMATIKANYA DALAM ALQUR’AN - Rahmat Zubarkah Nasution; Gunawan Gunawan (Pascasarjana UIN Sumatera Utara, 2021)
Humans have bodily and physiological functions that are no different from animals. However, cannot equate humans with animals because they have the advantage, namely reason. Ratio, talent to use language or language symbols, ability to laugh, ability to make tools, morality, character and so on are the characteristics that distinguish humans from animals. There are three concepts shown by the Qur'an when talking about humans, namely 1) al-basyar, 2) al-insan, 3). Bani Adam or Zurriyat Adam. Human position can be divided into two, namely (1). As khalifatullah fi al-ardh, (2). As 'Abdullah (servant of Allah). The first position means that humans are substitutes for God on earth. In this case, humans function as rulers and regulators on earth by applying God's laws. As servants of Allah, humans are required to worship and fulfil the function of individual human servants.